Kajian Bentuk Arsitektur Batak Toba dan Toraja sebagai Hasil Memori Kolektif Austronesia - Enrico Nirwan Histanto; Josephine Roosandriantini (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2024)
Title: Study of Toba and Toraja Batak Architectural Forms as a Result of Collective Austronesian Memory The archipelago (Indonesia) that we live in today is the distribution of the Austronesian people who lived in riverine areas in South China and North Vietnam in the mid-4th BC. Cultural development in an area results from a mixture of internal and external things. The mixing of culture and art by early settlers and new settlers resulted in diverse architectural forms, even though they share the same principles of traditional values (Austronesian collective memory). Toba and Toraja Batak architecture is hollow architecture with a similar roof shape that resembles the shape of a boat, a typology of houses and barns facing each other, and a housing complex oriented to form a particular axis. This research used an exploratory-qualitative approach, using literature sources combined with direct observations in the field. This research aims to find the level of closeness between Toba and Toraja Batak architecture based on the collective memory of the Austronesian people.